3D printing of silicon carbide - Tan, Richard Yong Heng (2018)
Additive Manufacturing (AM), has increasingly been gaining popularity in the world of manufacturing due to the myriad advantages it encompasses. There is a variety of AM, and each AM is constructed with different raw materials in printing products to meet its specialised purposes for different uses. Likewise, different AM requires different raw material in printing the product. The resources selected for AM ranges widely from non-metallic to metallic material. Therefore, finding the right proportion of each material in creating the mixture is extremely essential.